2014
DOI: 10.1111/ibi.12159
|View full text |Cite
|
Sign up to set email alerts
|

Strong temporal consistency in the individual foraging behaviour of Imperial Shags Phalacrocorax atriceps

Abstract: Individual consistency in foraging behaviour can generate behavioural variability within populations and may, ultimately, lead to species diversification. However, individualbased long-term behavioural studies are particularly scarce in seabird species. Between 2008 and 2011, breeding Imperial Shags Phalacrocorax atriceps at the Punta Le on colony, Argentina, were tracked with GPS devices to evaluate behavioural consistency during their foraging trips. Within a breeding season, individuals were highly consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 49 publications
9
42
1
Order By: Relevance
“…Other species from the blue-eyed shag complex show dietary specialisations that can be maintained over long timescales, consistent with the ability of some animals to adopt long-term behavioural strategies [3, 20, 32, 33]. …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Other species from the blue-eyed shag complex show dietary specialisations that can be maintained over long timescales, consistent with the ability of some animals to adopt long-term behavioural strategies [3, 20, 32, 33]. …”
Section: Discussionmentioning
confidence: 69%
“…The difference in consistency in maximum depths between males and females, however, is in line with values reported in [20, 56] who proposed differential degrees of individual specialisation within sexes as a mechanism for vertical niche partitioning. Harris et al did not report differences in consistency between sexes in the depth of area-restricted search (ARS) areas but identified differences in consistency in other aspects of the foraging behaviour of the Imperial shags they instrumented; indeed females were more consistent in the maximum distances reached from the colony and the shore [33]. They suggested that these differences might be linked with sexual dimorphism, which constrains one sex more than the other and reduces their behavioural plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that gentoos stay consistent in some aspects of their foraging behaviour, which may help to reduce intra-specific competition and/or may allow individuals to catch prey they can easily handle and digest (Bolnick et al 2003, Estes et al 2003. This seems particularly relevant in inshore foragers, as they are restricted in their foraging range (Cook et al 2006, Ratcliffe et al 2013, Harris et al 2014.…”
Section: Discussionmentioning
confidence: 96%
“…In order to quantify the intra-individual variation in diving behaviour and spatial use, we used the R package ape (Paradis et al 2004) to perform a variance component analysis. This method calculates the variance, standard deviation and proportion of total variance occurring at the levels of individual, and trip within individual when multiple observations per trip were obtained, as well as the residual variation (Ratcliffe et al 2013, Harris et al 2014). An estimate of individual specialisation is given by the proportion of variance explained by the individual variance component (Bolnick et al 2003, Dingemanse & Dochtermann 2013, Ratcliffe et al 2013).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We found marked inter-annual variation in all biochemical parameters analyzed in Imperial Cormorant chicks. Although previous studies in the same colony showed that foraging behavior and feeding locations of breeding Imperial Cormorants are highly consistent within and between breeding seasons (Quintana et al 2011;Harris et al 2014), part of the inter-annual variability in chick chemistries may be explained by differential nutrient profiles of prey consumed by parents (see also Gonz谩lez Miri and Malacalza 1999). Also contrary to our expectations, the breeding season that showed the highest mean values for plasma biochemistries (2011) coincided with that of lower productivity of the colony in terms of number of chicks fledged (based on average estimates over a period of 9 years; W. S. Svagelj and F. Quintana, unpubl.…”
Section: Discussionmentioning
confidence: 95%